HUBUNGAN PENURUNAN FUNGSI GERAK SENDI DENGAN TINGKAT STRES PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA GAU MABAJI KABUPATEN GOWA - haikal alpin; Rosita; Muhammad Haris (Stikes Graha Edukasi Makassar, 2021)
Decreased movement function in old age will have an impact on daily activity habits. The impact of these changes is the emergence of stress in the elderly. Some sources of stress are the environment. Elderly with decreased physical then he must adapt to the surrounding environment. In general, this study aims to determine the relationship between decreased joint movement and stress levels in the elderly at the Tresna Werda Gau Mabaji Social Institution, Gowa Regency in 2019. This type of research was non-experimental with a cross-sectional design. The sampling method is purposive sampling, with a total sample of 36 people from 100 respondents. The results of the analysis using the Pearson correlation test obtained a value of p = 0.000 which is smaller than the p value of 0.05. This shows that there is a significant relationship between decreased joint function and stress levels in the elderly at the Tresna Werdha Gau Mabaji Social Institution, Gowa Regency, while the value of r = 0.912 shows a positive correlation with a very strong correlation strength. Based on the research above, it can be concluded that there is a relationship between decreased joint motion function and stress levels in the elderly. As for suggestions for nurses, it is best to provide counseling to the elderly to do regular exercise so that the elderly avoid movement function or decreased function of muscle cells which can cause the elderly to experience stress